GARIS PANDUAN MENGEMUKAKAN PERSOALAN DAN MENGELUARKAN FATWA MENURUT AL-QUR’AN - Abd Rahman, Noor Naemah (Jurnal Syariah, 2019)
The mode of asking and issuing fatwa began in Muslim community by the revelation of Quran. However, it has not ended by the demise of the prophet (p.b.u.h). In fact, it is a continuous activity practiced in the society in order to seek guidance and hukm in accordance to Islam for each and everything happened in the community. In other word the issuance of fatwa is to guide Muslims to the right path of Islam. In process of issuing fatwa, every one has to pay an attention to the importance of Quran, for it, as a principal source of Islam has underlined general guidelines. Therefore, this article attempts to review methods used by the Quran in solving such a query pertaining to certain problems.